Africa/Brazil: bodies, time and silenced histories (Tempo e Argumento, 2009)
Considering that history is culture, the topics approached in this essay are connected to a fundamental claim for the incorporation of knowledges and powers from African and Afro-Brazilian oral traditions to our debates and historical constructions related to History of Africa and African and Afro- Brazilian cultures. Attempting tofollow historical movements of confrontation, negotiation and pressures between local knowledges and global projects, we try to face the traps presented by the construction and projection of eurocentric dominances.
Keywords: cultural disputes; oral traditions; body performances; rhythms; beliefs; diaspora